Explanatory factor analysıs on hurtt’s professıonal sceptıcısm scale: the example of turkey - Ahmet KARAHAN; Mehmet Kaygusuzoğlu (My University, 2021)
Professional scepticism is an approach to evaluating audit findings with a critical and questioning perspective. Professional scepticism is a feature that should be present to a certain degree in all members of the audit team during the audit work and is one of the factors that enable the audit to be performed effectively and with high performance. Professional scepticism must be applied throughout all stages of the audit. The concept of professional scepticism, which is an important determinant of audit quality, forms the basis of auditor independence and auditor opinion. According to the Independent Audit Standard 200, the auditor plans and conducts the audit with professional scepticism, recognizing that there may be circumstances that cause the financial statements to contain significant inaccuracies. Therefore, there is a need to measure professional scepticism in the audit. The most common scale used to measure professional scepticism is the scale developed by Hurtt (2010). Because of the importance of professional scepticism in the audit activity, the validity of this scale in the context of different countries needs to be tested. In this research the validity of Hurtt's professional scepticism scale in the context of the independent auditors operating in Turkey was examined by exploratory factor analysis. All of the variables in Hurtt's professional scepticism scale have produced significant results in determining professional scepticism in Turkey.
Keywords: Professional scepticism; Exploratory factor analysis; Auditing